Short-Term Steady-State Pattern Electroretinography Changes Using a Multi-Pressure Dial in Ocular Hypertensive, Glaucoma Suspect, and Mild Open-Angle Glaucoma Patients: A Randomized, Controlled, Prospective, Pilot Study - Jeremy J. Kudrna; Tanner J. Ferguson; Russell J. Swan; Steven J. Ferguson; Brandon J. Baartman; Adam R. Bleeker; Ramu G. Sudhagoni; John P. Berdahl; Michael D. Greenwood (Ophthalmology and Therapy, 2020)
Abstract Introduction This study evaluates the effects of the multi-pressure dial (MPD) on steady-state pattern electroretinography (ss-pERG) parameters. The study is a randomized, controlled, prospective, pilot trial in a private practice setting with ocular hypertensive (OHT), glaucoma suspect, and open-angle glaucoma (OAG) subjects. Methods This study included nine patients (64 ± 9.0 years, nine female) with OHT, glaucoma suspect, or mild OAG. One eye of each subject was randomized to receive negative periocular pressure, while the contralateral eye served as the intrasubject control through the goggle without negative pressure. The Diopsys High Contrast Sensitivity ss-pERG protocol was conducted on both eyes of each subject while wearing the MPD device. Application of negative periocular pressure was set at 50% of baseline intraocular pressure for each study eye. Results Following 2 h of negative periocular pressure application, the difference in MagnitudeD (MagD) from baseline for eyes randomized to receive negative periocular pressure (+ 0.17 versus  − 0.26) was statistically significant (p = 0.023). Over the same period, the change in MagD/Magnitude (MagD/Mag ratio) from baseline for eyes randomized to receive negative periocular pressure was also higher (+ 0.14 versus  − 0.16), compared to the control eyes, approached significance (p = 0.059). Conclusions Following 2 h of MPD wear, the measured MagD and MagD/Mag ratio improved compared to control, suggesting that negative periocular pressure application to the anterior globe can lead to short-term improvement in one measure of retinal ganglion cell function.